Can Housing Assets Affect the Chinese Residents’ Willingness to Pay for Green Housing? - Wu, Qian; Zheng, Ziyang; Li, Wenbo (Frontiers in Psychology, 2022)
As the development trend of future housing field, Green housing is an effective way to reduce pollution, save energy and promote industrial upgrading. At the same time, green house is of great significance to change the development mode of construction industry and promote the sustainable development of social economy. This study proposes a comprehensive research model that integrates residents’ happiness and personal traits to examine the influencing mechanism of residents’ intention to purchase Green buildings. The proposed model is empirically tested using data collected from 1338 urban residents in China. Based on Logit, Probit and Ivprobit models, factors such as personal characteristics, housing price and the number of real estate ownership are selected to conduct empirical analysis and mechanism analysis on willingness that affect consumers' purchase of green houses. The results show that housing assets significantly affect householders' willingness to pay for green house. And the more houses they own, the higher their willingness to pay for green house will be. Similarly, if the housing prices are higher, householders are more willing to buy green house. The amount of housing assets will affect the householder's willingness to pay for green housing through the way of individual happiness. In terms of the characteristics of the householder, if the householder is more educated, unmarried, his willingness to buy green house will be stronger，and owning housing assets may affect individual happiness, due to the housing wealth effect brought by rising housing prices, people with more housing assets are more likely to have the happiness brought by higher wealth, which may affect the purchase intention of householders.